Efeitos do transplante de menisco lateral na estabilidade e biomecânica do joelho: estudo robótico avaliando as técnicas de fixação com bloco ósseo e apenas com sutura - Novaretti, Joao Victor [UNIFESP] (2019)
Background: The ability of lateral meniscal allograft transplantation (MAT) to improve knee stability and the load-bearing function of the meniscus in a meniscectomized condition is critical for surgical success. Purpose: The purpose of this study was to compare the effects of two lateral MAT fixation techniques –bone block and suture-only– on translational and rotatory knee stability, resultant forces in the meniscal allograft, and in-situ force in the anterior cruciate ligament (ACL). Methods: Using a robotic testing system, loads (134 N anterior tibial load + 200 N axial compression, 5 Nm internal tibial torque + 5 Nm valgus torque, and 5 Nm external tibial torque + 5 Nm valgus torque) were independently and continuously applied during flexion of ten fresh-frozen cadaveric knees. Kinematics and forces data were recorded for four knee states: intact, total lateral meniscectomy, lateral MAT bone-block, and lateral MAT suture-only fixation techniques. A repeated measures analysis of variance (ANOVA) with a post-hoc Bonferroni correction was used to analyze the variations in kinematics and forces at 0º, 30º, 60º, and 90º of knee flexion. Significance was set at p <0.05. Results: When anterior loads were applied, both lateral MAT bone-block and sutureonly fixation techniques decreased medial translation of the tibia that was increased after total lateral meniscectomy at 30º, 60º and 90º of knee flexion by 54.2%, 48.0%, and 50.0%, and 50.0%, 40.0% and 34.6%, respectively (p <0.05). Resultant forces in the meniscal allograft were 50-60% of the resultant forces in the intact lateral meniscus in response to all loading conditions at all knee flexion angles (p <0.05). In-situ force in the ACL decreased up to 27.3% after total lateral meniscectomy (p <0.05), but no increase was observed after either lateral MAT technique (p >0.05). Overall, no significant differences between lateral MAT techniques were observed regarding kinematics and meniscal allograft and ACL forces (p >0.05). Conclusion: Lateral meniscal transplantation reduced medial translation of the tibia that was increased after total lateral meniscectomy in response to anterior loads. Resultant forces in the meniscal allograft were 50-60% of the intact lateral meniscus forces. In the majority of testing conditions, no significant changes of the in-situ force in the ACL were observed after total lateral meniscectomy. Both lateral MAT fixation techniques functioned similarly in response to the loading conditions.